Ball-milling catalytic hydrosilylation reaction method and used catalyst
By using Rh-Ni-Cu metal cladding grinding balls as catalysts, the silicon hydrogen addition reaction is catalyzed by ball milling, which solves the problems of cumbersome and high cost in the preparation process of the existing precious metal catalysts, and achieves efficient and stable catalytic performance and simplified preparation process.
Patent Information
- Application Number
- CN202411832572.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The preparation process of precious metal catalysts used in existing hydrogen silicon addition reactions is cumbersome, difficult to achieve industrialization, and has problems such as high cost, difficult operation and complex ligands.
The hydrogen silicon addition reaction of a variety of silicon-hydrogen bond-containing silanes or siloxanes with unsaturated hydrocarbons is catalyzed by ball milling method using Rh-Ni-Cu metal cladding grinding balls as catalysts. The catalyst is prepared by laser cladding technology, simplifying the preparation process of the catalyst and reducing costs.
It has achieved efficient catalysis of hydrogen silicon addition reaction, high raw material reaction rate and stable catalytic performance, simplified the preparation of catalysts and improved the feasibility of industrial applications, and met the requirements of sustainable development.
Smart Images

Figure BDA0005185888050000051 
Figure BDA0005185888050000052 
Figure BDA0005185888050000053
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical industry, in particular to the field of synthesis of organic silicon, and specifically relates to a ball milling catalyzed hydrosilylation reaction of multiple silanes or siloxanes containing silicon-hydrogen bonds with unsaturated hydrocarbons. Background Art
[0002] The hydrosilylation reaction is an addition reaction between silane compounds containing silicon hydrogen and unsaturated compounds under certain conditions. It is the most typical reaction to generate Si-C bonds. It is simple to operate, has mild conditions, few side reactions, and pure products. It is extremely beneficial to modern industrial production.
[0003] The catalysts used in early hydrosilylation were mainly noble metals such as Rh, Pt, Ir, and Ru, such as Karstedt catalyst and Speier catalyst, which are all Pt-containing catalysts (Angewandte Chemie International Edition, 2020, 60(2):550-565). These noble metal catalysts often have high catalytic activity, but have disadvantages such as high price, difficult operation, and complex ligands.
[0004] For example, in the application of olefin hydrosilylation reaction of olefin and hydrosilane disclosed in patent CN 113399001A, platinum series catalyst is used under nitrogen protection, the temperature is slowly raised, triethylhydrosilane (1 mol) is added dropwise through a dropping funnel, the reaction temperature is maintained, the stirring reaction is continued for several hours, the reaction is cooled to room temperature, the corresponding components are collected by vacuum distillation, and finally the conversion rate of hexene is determined by GC-MS. The disadvantages of this method are: the catalyst preparation process of this method is cumbersome, and the preparation process is difficult to realize industrialization.
[0005] Seeking non-precious metal compounds (such as nickel, iron, cobalt, titanium, etc.) to replace precious metal catalysts has always been a focus in the field of catalytic chemistry research.
[0006] Taking the olefin hydrosilylation reaction as an example, Ni can be used as a catalyst to catalyze the hydrosilylation reaction of terminal olefins and hydrogen-containing siloxanes very efficiently. The products generated are mainly anti-Markovnikov addition products. In this catalytic reaction, 1 H NMR and 29Si NMR detected Ni-silane intermediates. Therefore, in this reaction process, the active site is the Ni-Si intermediate formed by the combination of Ni and silane, rather than the Ni-H intermediate.
[0007] Mechanochemistry is an emerging discipline that studies the chemical reactions, physicochemical properties or internal microstructure changes of materials induced and acted upon by mechanical forces. For most chemical syntheses, the reaction is carried out in solution; while mechanochemistry that relies on mechanical forces basically does not require solvents, has low energy consumption, fast reaction speed, and can basically react and synthesize a series of functional molecules quantitatively. For example, patent CN 117209527A discloses a method for preparing a metal catalyst clad on the surface of a grinding ball using laser cladding technology, and uses mechanochemistry to synthesize organosilanes. However, there are currently no reports on the use of ball milling to catalyze hydrosilylation reactions. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a ball milling catalytic hydrosilylation reaction method and the catalyst used. The method uses Rh-Ni-Cu metal cladding layer grinding balls as catalysts and uses ball milling to catalyze the hydrosilylation reaction of various silanes or siloxanes containing silicon-hydrogen bonds with unsaturated hydrocarbons.
[0009] That is, the present invention provides a method for preparing a Rh-Ni-Cu clad grinding ball on one hand, and provides a use of the grinding ball for applying it to the hydrosilylation ball milling reaction of unsaturated compounds such as olefins, alkynes and carbonyl compounds on the other hand.
[0010] In order to solve the above technical problems, the present invention provides a method for preparing a Rh-Ni-Cu cladding layer grinding ball, comprising the following steps:
[0011] 1) Grinding ball pretreatment:
[0012] The grinding balls are polished to remove surface dirt and oxide layers, and then cleaned and dried (for example, at 70±10° C. for about 1±0.2 hours) to obtain treated grinding balls;
[0013] 2) Rh-Ni-Cu alloy material configuration:
[0014] Powdered Rh, Ni and Cu are placed in a mixer to mix to form alloy powder, and then dried (i.e., the powder is dried before cladding, at 70±10° C. for about 1±0.2 hours) to obtain dry alloy powder;
[0015] In the alloy powder, the content of Rh is 3wt%, the content of Ni is 62-82wt%, and the content of Cu is 15-35wt%;
[0016] 3) Grinding ball cladding:
[0017] The dry alloy powder obtained in step 2) is bonded to the surface of the treated grinding ball obtained in step 1) with a binder, and dried with hot air (so that the binder is evaporated, for example, hot air drying at 80±10°C for 30±5 minutes), and then preheated to 170-180°C, and then placed on a cladding workbench, and the surface of the grinding ball is laser clad to obtain a metal cladding layer grinding ball.
[0018] As an improvement of the preparation method of the Rh-Ni-Cu cladding layer grinding ball of the present invention, in the step 3):
[0019] The process parameters of laser cladding are: laser power of 800-2000W (preferably 1000-1500W), spot diameter of 3-5mm (preferably 4mm), scanning speed of 5-7mm / s (preferably 6mm / s), overlap rate of 40-60% (preferably 50%), powder feeding speed of 7-9g / min (preferably 8g / min);
[0020] The average thickness of the laser coating is 1.0 to 1.2 mm.
[0021] As a further improvement of the method for preparing the Rh-Ni-Cu cladding layer grinding ball of the present invention, in step 1):
[0022] The material of the grinding ball is 303 stainless steel, 304 stainless steel, tungsten carbide or zirconium oxide, and the particle size of the grinding ball is 25mm~45mm (spherical);
[0023] Grind the grinding ball with 200-500 mesh sandpaper and clean it with pure water and ethanol.
[0024] As a further improvement of the method for preparing the Rh-Ni-Cu cladding layer grinding ball of the present invention, in step 3): each grinding ball is equipped with 10 to 35 g of dried alloy powder.
[0025] As a further improvement of the method for preparing the Rh-Ni-Cu cladding layer grinding ball of the present invention,
[0026] The preferred formula of the alloy powder in step 2) is: 3wt% Rh, 77wt% Ni, 20wt% Cu.
[0027] As a further improvement of the method for preparing the Rh-Ni-Cu cladding layer grinding ball of the present invention,
[0028] When the particle size of the grinding ball is 25 mm, each grinding ball is equipped with 10 to 13 g of dry alloy powder;
[0029] When the particle size of the grinding ball is 35 mm, each grinding ball is equipped with 15 to 18 g of dry alloy powder;
[0030] When the particle size of the grinding ball is 45 mm, each grinding ball is equipped with 30 to 35 g of dry alloy powder.
[0031] As a further improvement of the preparation method of the Rh-Ni-Cu cladding layer grinding ball of the present invention, the binder is prepared by mixing 502 glue and acetone in a volume ratio of 1:14-16, and the mass ratio of dry alloy powder: binder = 1: (1±0.1).
[0032] The present invention also provides a hydrogen addition method, using the Rh-Ni-Cu cladding layer grinding ball prepared by any of the above methods as a catalyst, comprising the following steps:
[0033] Rh-Ni-Cu clad grinding balls as catalysts and reaction materials for hydrosilylation are placed in a ball mill; the reaction materials are composed of a compound containing a Si-H bond (organosilane) and an unsaturated substance (for example, an unsaturated hydrocarbon); the molar ratio of the unsaturated substance to the compound containing a Si-H bond is 1: (1.2±0.1);
[0034] The reaction mixture is ball-milled at room temperature for 5 to 10 hours (preferably 7 to 10 hours) at a reaction pressure of 0.1 to 1 MPa and a rotation speed of 700 to 1000 rpm. After the reaction is completed, the reaction mixture in the ball mill is taken out and filtered to obtain a filtrate and a filter cake respectively. The filter cake is rinsed with ethanol to obtain a washing liquid. The washing liquid and the filtrate are combined and distilled to obtain a hydrosilylation product.
[0035] As an improvement of the hydrosilylation method of the present invention: (300±20) g of metal cladding grinding balls prepared from dry alloy powder are used for every 1.0 mol of unsaturated substance.
[0036] Specifically, grinding balls containing 300±20g of dry alloy powder are placed in a ball mill jar with a volume of 1.5L. The number of grinding balls is 10 to 30, specifically 10 (45mm), 20 (35mm), and 30 (25mm).
[0037] As an improvement of the hydrosilylation method of the present invention:
[0038] The unsaturated compound is any one of the following: pentene, hexene, heptene, styrene, heptyne, octyne, phenylacetylene, propionaldehyde, butyraldehyde, benzaldehyde, acetone, butanone, acetophenone;
[0039] The compound containing Si-H bonds is any one of the following: dimethylchlorosilane, methyldichlorosilane, phenylsilane, diphenylsilane, trimethoxysilane, and triethoxysilane.
[0040] The present invention prepares grinding balls with metal catalysts clad on the surface and develops a process for downstream products of hydrosilylation by ball milling. The technical advantages are:
[0041] 1. The present invention utilizes laser cladding technology to prepare a metal catalyst clad on the surface of a grinding ball. When the catalyst is used for a hydrosilylation reaction, it exhibits excellent catalytic performance, a high raw material reaction rate, stable catalytic performance, and is easy to collect and process.
[0042] 2. The method of using metal powder directly as a catalyst to catalyze the hydrosilylation reaction of olefins and hydrogen-containing silanes can simplify the preparation of hydrosilylation catalysts and reduce the cost of hydrosilylation reactions. In addition, the new process synthesized by mechanochemical methods is more in line with the requirements of sustainable development, which can basically achieve atomic economy in hydrosilylation reactions and promote green and efficient production of hydrosilylation reactions in the chemical industry.
[0043] In summary, the method of the present invention using metal powder directly as a catalyst to catalyze the hydrosilylation reaction of olefins and hydrogen-containing silanes can simplify the preparation of the hydrosilylation catalyst and reduce the cost of the hydrosilylation reaction. In addition, the new process synthesized by mechanochemical method can promote the green and efficient production of hydrosilylation reaction in the chemical industry. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0045] The particle sizes of the metals Rh, Ni and Cu in the alloy powder are all 25 to 50 μm and the shapes are spherical.
[0046] The products obtained in the following cases were verified by conventional NMR to verify their correctness.
[0047] Embodiment 1: A method for ball milling catalytic hydrosilylation reaction, comprising the following steps in sequence:
[0048] 1) Pretreatment of grinding balls: Take 30 zirconia grinding balls with a diameter of 25 mm, and use 500-mesh sandpaper to polish the surface of the zirconia grinding balls. The polishing requires to completely remove the surface dirt and oxide layer, that is, remove the oxide film on the surface of the grinding ball until there are no coarse scratches, the direction of the scratches is consistent and the surface is bright. After cleaning with ethanol, put it in a 70°C drying oven for 1 hour to obtain the polished grinding balls (treated grinding balls) for standby use.
[0049] 2) Alloy powder material configuration:
[0050] The alloy powder is composed of Rh3wt%, Ni77wt% and Cu20wt% in weight proportion.
[0051] Weigh the alloy powder, and then mix it in a dry powder mixer for 3 hours so that Rh, Ni, and Cu can be evenly mixed, and dry it at 70°C for about 1 hour (the purpose of drying is to remove possible moisture in the alloy powder to facilitate subsequent bonding to the grinding ball) to obtain dry alloy powder; set aside.
[0052] 3) Grinding ball cladding:
[0053] Evenly mix 502 glue and acetone in a volume ratio of 1:15 to obtain an adhesive;
[0054] 300 g of the dry alloy powder obtained in step 2) is mixed with an equal mass of a binder to form a paste, and then evenly coated on the surface of the polished grinding ball obtained in step 1), and blown dry with hot air (blow dried with hot air at 80°C for 30 minutes to evaporate the binder); a grinding ball coated with alloy powder is obtained.
[0055] The grinding ball coated with alloy powder was preheated to 160°C and then fixed on the laser cladding workbench. The process parameters of laser cladding were set as follows: laser power of 1000 W, spot diameter of 4 mm, scanning speed of 6 mm / s, overlap rate of 50%, powder feeding speed of 8 g / min. A Rh-Ni-Cu cladding layer was obtained on the surface of the grinding ball with an average thickness of about 1 mm. The obtained layer was named as the clad grinding ball.
[0056] 4) Ball milling reaction:
[0057] Put all the clad grinding balls obtained in step 3) into a ball mill (1.5L), put a raw material consisting of 1.0 mol of pentene (1-pentene) and 1.2 mol of trimethoxysilane into the ball mill (i.e., the molar ratio of pentene:trimethoxysilane = 1:1.2), and perform mechanical ball milling for 8 hours. The ball mill pressure is 0.1 MPa and the ball mill speed is 1000 rpm.
[0058] After the reaction is completed, the reaction mixture in the ball mill is taken out and filtered to obtain a filtrate. The solid obtained after filtration is rinsed with ethanol three times to obtain a washing liquid. The washing liquid and the filtrate are mixed and distilled to collect the fraction at 175-185°C to obtain n-pentyltrimethoxysilane.
[0059] The results obtained were: pentene conversion rate of 86.7%, and product n-pentyltrimethoxysilane selectivity of 92.3%.
[0060]
[0061]
[0062] Description: B is the molar mass of pentene added to the reaction system, mol;
[0063] n B ' is the molar mass of pentene in the reaction system after the reaction, mol;
[0064] n C ' is the molar mass of the product n-pentyltrimethoxysilane in the reaction system after the reaction, mol.
[0065] Example 2-4: Compared with Example 1, the ratio of Rh, Ni and Cu in the alloy powder is changed, and the total amount of the alloy powder remains unchanged; other operations are the same as Example 1, and Example 2-4 is obtained. The process parameters and reaction results are shown in Table 1.
[0066] Table 1
[0067]
[0068] Example 5-6: Compared with Example 1, the particle size and the corresponding number of grinding balls were changed, and other operations were the same as Example 1. See Table 2 for process parameters and reaction results.
[0069] Table 2
[0070]
[0071]
[0072] Examples 7-11, relative to Example 1, the ball milling time in step 4) was changed, and other operations were the same as Example 1. See Table 3 for process parameters and reaction results.
[0073] Table 3
[0074]
[0075] Examples 12-16: Compared with Example 1, the ball milling speed in step 4) was changed, and other operations were the same as Example 1. See Table 4 for process parameters and reaction results.
[0076] Table 4
[0077]
[0078] Example 17 series, changing the reaction raw materials to carry out olefin hydrosilylation reaction, specifically as follows:
[0079] Example 17-1. Compared with Example 1, the raw materials are changed to 1.0 mol of heptene and 1.2 mol of triethoxysilane, and distillation is performed to select the fraction at 80-90° C.; the rest is the same as Example 1.
[0080] The heptene conversion rate was 92.6%, and the selectivity of the product n-heptyltriethoxysilane was 98.9%.
[0081] Example 17-2: Compared with Example 1, the raw materials are changed to 1.0 mol of pentene and 1.2 mol of dimethylchlorosilane, and distillation is performed to select the fraction of 160-170°C; the rest is the same as Example 1.
[0082] The conversion rate of pentene was 78.3%, and the selectivity of the product n-pentyldimethylchlorosilane was 97.7%.
[0083] Example 17-3: Compared with Example 1, the raw materials are changed to 1.0 mol of heptene and 1.2 mol of methyldichlorosilane, and distillation is performed to select the fraction at 200-210°C; the rest is the same as Example 1.
[0084] The heptene conversion rate was 82.6%, and the selectivity of the product n-heptylmethyldichlorosilane was 85.8%.
[0085] Example 17-4: Compared with Example 1, the raw materials are changed to 1.0 mol of styrene and 1.2 mol of dimethylchlorosilane, and distillation is performed to select the fraction at 50-60°C; the rest is the same as Example 1.
[0086] The styrene conversion rate was 87.9%, and the selectivity of the product phenylethyldimethylsilyl chloride was 93.7%.
[0087] Example 17-5: Compared with Example 1, the raw materials are changed to 1.0 mol of heptylene and 1.2 mol of dimethylchlorosilane, and distillation is performed to select the fraction at 225-235°C; the rest is the same as Example 1.
[0088] The heptylene conversion rate was 95.7%, and the selectivity of the product heptyldimethylsilyl chloride was 97.8%.
[0089] Example 17-6: Compared with Example 1, the raw materials are changed to 1.0 mol of octyne and 1.2 mol of trimethoxysilane, and distillation is performed to select the fraction at 250-270°C; the rest is the same as Example 1.
[0090] The octyne conversion rate was 94.2%, and the selectivity of the product octenyltrimethoxysilane was 90.3%.
[0091] Example 17-7: Compared with Example 1, the raw materials are changed to 1.0 mol of phenylacetylene and 1.2 mol of dimethylchlorosilane, and distillation is performed to select the fraction at 78-88°C; the rest is the same as Example 1.
[0092] The conversion rate of phenylacetylene was 93.2%, and the selectivity of the product styryldimethylsilyl chloride was 94.6%.
[0093] Example 17-8: Compared with Example 1, the raw materials are changed to 1.0 mol of phenylacetylene and 1.2 mol of trimethoxysilane, and distillation is performed to select the fraction at 95-105°C; the rest is the same as Example 1.
[0094] The conversion rate of phenylacetylene was 96.2%, and the selectivity of the product styryltrimethoxysilane was 92.3%.
[0095] Example 18 series, the reaction raw materials are changed to carry out aldehyde hydrosilylation reaction, specifically as follows:
[0096] Example 18-1: Compared with Example 1, the raw materials are changed to 1.0 mol of propionaldehyde and 1.2 mol of trimethoxysilane, and distillation is performed to select the fraction of 137-147°C; the rest is the same as Example 1.
[0097] The conversion rate of propionaldehyde was 93.2%, and the selectivity of the product propoxytrimethoxysilane was 94.5%.
[0098] Example 18-2: Compared with Example 1, the raw materials are changed to 1.0 mol of butyraldehyde and 1.2 mol of triethoxysilane, and distillation is performed to select the fraction at 175-185°C; the rest is the same as Example 1.
[0099] The butyraldehyde conversion rate was 95.3%, and the product butoxytriethoxysilane selectivity was 96.2%.
[0100] Example 18-3: Compared with Example 1, the raw materials are changed to be composed of 1.0 mol of benzaldehyde and 1.2 mol of phenylsilane, and distillation is performed to select the fraction at 180-190°C; the rest is the same as Example 1.
[0101] The benzaldehyde conversion rate was 97.5%, and the selectivity of the product benzyloxyphenylsilane was 95.4%.
[0102] Example 18-4: Compared with Example 1, the raw materials are changed to be composed of 1.0 mol of benzaldehyde and 1.2 mol of triethoxysilane, and distillation is performed to select the fraction at 230-240°C; the rest is the same as Example 1.
[0103] The conversion rate of benzaldehyde was 94.7%, and the selectivity of the product benzyloxytriethoxysilane was 92.6%.
[0104] Example 19 series, changing the reaction raw materials to carry out ketone hydrosilylation reaction, specifically as follows:
[0105] Example 19-1. Compared with Example 1, the raw materials are changed to 1.0 mol of acetone and 1.2 mol of diphenylsilane, and distillation is performed to select the fraction at 180-190°C; the rest is the same as Example 1.
[0106] The acetone conversion rate was 91.4%, and the selectivity of the product isopropoxydiphenylsilane was 95.2%.
[0107] Example 19-2: Compared with Example 1, the raw materials are changed to 1.0 mol of butanone and 1.2 mol of trimethoxysilane, and distillation is performed to select the fraction at 235-245°C; the rest is the same as Example 1.
[0108] The butanone conversion rate was 92.5%, and the product trimethoxy-sec-butoxysilane selectivity was 93.1%.
[0109] Example 19-3: Compared with Example 1, the raw materials are changed to 1.0 mol of acetophenone and 1.2 mol of diphenylsilane, and distillation is performed to select the fraction at 155-165°C; the rest is the same as Example 1.
[0110] The acetophenonation rate was 92.7%, and the selectivity of the product diphenyl-[(methoxyphenyl)methoxy]silane was 94.8%.
[0111] Example 20: The process parameters of laser cladding in step 3) were changed as follows: laser power 800 W, spot diameter 4 mm, scanning speed 6 mm / s, overlap rate 50%, powder feeding speed 8 g / min, and the rest were the same as Example 1. The results were as follows: pentene conversion rate 70.2%, product n-pentyltrimethoxysilane selectivity 83.4%.
[0112] Example 21: The process parameters of laser cladding in step 3) were changed as follows: laser power of 1500 W, spot diameter of 4 mm, scanning speed of 6 mm / s, overlap rate of 50%, powder feeding speed of 8 g / min, and the rest were the same as in Example 1. The results obtained were: pentene conversion of 80.9%, and selectivity of product n-pentyltrimethoxysilane of 89.7%.
[0113] Comparative Example 1: The "hot air drying" in step 3) of Example 1 was omitted, that is, the coated grinding balls were preheated to 160°C and then fixed on the laser cladding workbench; the rest was the same as Example 1. The results obtained were: pentene conversion rate of 75.6%, and product n-pentyltrimethoxysilane selectivity of 85.3%.
[0114] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a Rh-Ni-Cu cladding layer grinding ball, characterized in that The steps include: 1) Grinding ball pretreatment: The grinding balls are polished to remove dirt and oxide layers on the surface, and then cleaned and dried to obtain treated grinding balls; 2) Rh-Ni-Cu alloy material configuration: Powdered Rh, Ni and Cu are placed in a mixer to mix to form alloy powder, and then dried to obtain dry alloy powder; In the alloy powder, the content of Rh is 3wt%, the content of Ni is 62-82wt%, and the content of Cu is 15-35wt%; 3) Grinding ball cladding: The dry alloy powder obtained in step 2) is bonded to the surface of the treated grinding ball obtained in step 1) with a binder, dried with hot air, preheated to 170-180° C., and then placed on a cladding workbench to perform laser cladding on the surface of the grinding ball to obtain a metal cladding layer grinding ball.
2. The method for preparing the Rh-Ni-Cu cladding layer grinding ball according to claim 1, characterized in that In the step 3): The process parameters of laser cladding are: laser power of 800-2000W, spot diameter of 3-5mm, scanning speed of 5-7mm / s, overlap rate of 40-60%, and powder feeding speed of 7-9g / min.
3. The method for preparing the Rh-Ni-Cu cladding layer grinding ball according to claim 2, characterized in that In the step 1): The material of the grinding ball is 303 stainless steel, 304 stainless steel, tungsten carbide or zirconium oxide, and the particle size of the grinding ball is 25mm~45mm; Grind the grinding ball with 200-500 mesh sandpaper and clean it with pure water and ethanol.
4. The method for preparing the Rh-Ni-Cu cladding layer grinding ball according to claim 3, characterized in that In the step 3), each grinding ball is equipped with 10 to 35 g of dried alloy powder.
5. The method for preparing a Rh-Ni-Cu cladding layer grinding ball according to any one of claims 1 to 4, characterized in that: The formula of the alloy powder in step 2) is: Rh 3wt%, Ni 77wt%, Cu 20wt%.
6. The method for preparing a Rh-Ni-Cu clad grinding ball according to any one of claims 1 to 5, characterized in that: When the particle size of the grinding ball is 25 mm, each grinding ball is equipped with 10 to 13 g of dry alloy powder; When the particle size of the grinding ball is 35 mm, each grinding ball is equipped with 15 to 18 g of dry alloy powder; When the particle size of the grinding ball is 45 mm, each grinding ball is equipped with 30 to 35 g of dry alloy powder.
7. The method for preparing a Rh-Ni-Cu clad grinding ball according to any one of claims 1 to 6, characterized in that: The binder is prepared by mixing 502 glue and acetone in a volume ratio of 1:14-16; the mass ratio of dry alloy powder: binder is 1:(1±0.1).
8. A hydrosilylation method, characterized in that: The Rh-Ni-Cu cladding layer grinding ball prepared by any one of the methods of claims 1 to 7 is used as a catalyst, comprising the following steps: A ball mill is loaded with Rh-Ni-Cu clad grinding balls as a catalyst and reaction materials for hydrosilylation; the reaction materials are composed of compounds containing Si-H bonds and unsaturated substances; the molar ratio of unsaturated substances to compounds containing Si-H bonds is 1: (1.2±0.1); The reaction mixture is ball-milled at room temperature for 5 to 10 hours at a reaction pressure of 0.1 to 1 MPa and a rotation speed of 700 to 1000 rpm. After the reaction is completed, the reaction mixture in the ball mill is taken out and filtered to obtain a filtrate and a filter cake respectively. The filter cake is rinsed with ethanol to obtain a washing liquid. The washing liquid and the filtrate are combined and then distilled to obtain a hydrosilylation product.
9. The hydrosilylation method according to claim 8, characterized in that: The metal cladding layer grinding balls prepared by using (300±20) g of dry alloy powder are used for every 1.0 mol of unsaturated substances.
10. The hydrosilylation method according to claim 9, characterized in that: The unsaturated compound is any one of the following: pentene, hexene, heptene, styrene, heptyne, octyne, phenylacetylene, propionaldehyde, butyraldehyde, benzaldehyde, acetone, butanone, acetophenone; The compound containing Si-H bonds is any one of the following: dimethylchlorosilane, methyldichlorosilane, phenylsilane, diphenylsilane, trimethoxysilane, and triethoxysilane.
Citation Information
Patent Citations
Catalyst for olefin hydrosilylation reaction, preparation method and application thereof
CN113399001A
Three-dimensional micro / nano hierarchically-structured cobalt-aluminium hydrotalcite material, and preparation method and applications thereof
CN103601255A
Method for preparing silica powder through mechanical chemical method
CN105271238A
Preparation method of dimethyl hydrogen chlorosilane
CN106632447A
Method for preparing organosilane by silicon powder ball-milling catalysis method
CN117209527A